Ipilimumab for the treatment of advanced melanoma in six kidney transplant patients. Issue 12 (21st September 2018) - Zehou, Ouidad; Leibler, Claire; Arnault, Jean‐Philippe; Sayegh, Johnny; Montaudié, Henri; Rémy, Philippe; Glotz, Denis; Cordonnier, Carole; Martin, Ludovic; Lebbé, Céleste
Abstract: Immune checkpoint inhibitors are new therapeutic options for metastatic melanoma, but few data are available in organ transplant recipient populations. Six French patients, three men and three women, mean age 66 years (range 44‐74), all kidney transplant recipients, received ipilimumab (CTLA‐4 inhibitor) for metastatic melanoma. At diagnosis of advanced melanoma, immunosuppressive therapy had been minimized in all but one. Adverse effects included one case of grade 1 diarrhea and one of grade 1 pruritus. One patient had acute T cell–mediated rejection confirmed by histology after the first injection of ipilimumab. After a median follow‐up of 4.5 (3‐20) months, one patient achieved partial response, one had stable disease, and four had disease progression. All the patients died, five from melanoma, one from another cause. In this series and in the literature, ipilimumab proved to be safe and possibly active. The acute rejection we encountered was probably related to both a rapid, drastic reduction of immunosuppression and the use of ipilimumab. Our safety data on ipilimumab contrast with the organ transplant rejections already reported with PD‐1 inhibitors. We consider that immunosuppression should not be minimized, as the impact on metastatic disease control is probably small. Abstract : In this French national retrospective study of six organ transplant recipients treated for metastatic melanoma, the immune checkpoint inhibitor ipilimumab showed some efficacy and one case of organ rejection, suggesting that immunosuppression alterations should be carefully discussed and probably avoided, as the impact on metastatic disease control is probably small.